In vitro Cartilage Regeneration Regulated by a Hydrostatic Pressure Bioreactor Based on Hybrid Photocrosslinkable Hydrogels - Zhao, Xintong; Hua, Yujie; Wang, Tao; Ci, Zheng; Zhang, Yixin; Wang, Xiaoyun; Lin, Qiuning; Zhu, Linyong; Zhou, Guangdong (Frontiers in Bioengineering and Biotechnology, 2022)
Because of the superior characteristics of photocrosslinkable hydrogels suitable for 3D cell-laden bioprinting, tissue regeneration based on photocrosslinkable hydrogels has become an important research topic. However, due to nutrient permeation obstacles caused by the dense networks and static culture conditions, there have been no successful reports on in vitro cartilage regeneration with certain thicknesses based on photocrosslinkable hydrogels. To solve this problem, hydrostatic pressure (HP) provided by the bioreactor was used to regulate the in vitro cartilage regeneration based on hybrid photocrosslinkable (HPC) hydrogel. Chondrocyte laden HPC hydrogels (CHPC) were cultured under 5 MPa HP for 8 weeks and evaluated by various staining and quantitative methods. Results demonstrated that CHPC can maintain the characteristics of HPC hydrogels and is suitable for 3D cell-laden bioprinting. However, HPC hydrogels with concentrations over 3% wt% significantly influenced cell viability and in vitro cartilage regeneration due to nutrient permeation obstacles. Fortunately, HP completely reversed the negative influences of HPC hydrogels at 3% wt%, significantly enhanced cell viability, proliferation, and extracellular matrix (ECM) deposition by improving nutrient transportation and up-regulating the expression of cartilage-specific genes, and successfully regenerated homogeneous cartilage with a thickness over 3 mm. The transcriptome sequencing results demonstrated that HP regulated in vitro cartilage regeneration primarily by inhibiting cell senescence and apoptosis, promoting ECM synthesis, suppressing ECM catabolism, and ECM structure remodeling. Evaluation of in vivo fate indicated that in vitro regenerated cartilage in the HP group further developed after implantation and formed homogeneous and mature cartilage close to the native one, suggesting significant clinical potential. The current study outlines an efficient strategy for in vitro cartilage regeneration based on photocrosslinkable hydrogel scaffolds and its in vivo application.